Drivers of liking in men’s skin care across cultures - Deubler, Grace Isabella (Kansas State University, 2021)
The male consumer has long been ignored in the skincare space. Times are changing and this demographic has become more open and interested in traditionally feminine beauty and skin care products. This dissertation aims to begin creating a body of knowledge regarding sensory and consumer research on men’s personal care products by identifying drivers of liking in the face lotion category and subsequently exploring the male skincare consumer. In Phase I, eighteen interviews were conducted in two markets, Kansas City and Los Angeles, to understand the baseline information on men’s perceptions, opinions, beliefs, and attitudes related to skin care. Men recruited for the interviews were between the ages 18-49 and were willing to try new skin care products. The key take-aways from this research included that men generally appreciate easy, fast skin care routines, use affordable and readily available products, and desire to maintain the look and/or health of their skin. A sorting task completed during the interviews provided the researcher with information on men’s perceptions of different brands and commercially available products. Based on these learnings, 12 lotion products were selected for further research based on their perceived relevance to the male skin care consumer. In Phase II, descriptive analysis was performed by six highly trained panelists at the Kansas State Sensory and Consumer Research Center. A consensus-based modified flavor/texture profile method was used. The panel evaluated for 48 attributes across five modalities: appearance, aroma, pick up, rubout, and afterfeel. This evaluation differentiated across the products and demonstrated the key similarities and differences; this was made clear as the results were visualized via cluster analysis and principal component analysis. The men’s face lotion samples tended to have more masculine scents and thicker textures compared to gender neutral or feminine-leaning products. In Phase III, a home use test was conducted on eight products – selected for their differentiated profiles according to the descriptive analysis – to determine drivers of liking for men’s face lotion. The research was conducted in two markets: Olathe, KS, USA and Seoul, Republic of Korea. Products were tested by 80 male participants in each country in an incomplete randomized block design; each panelist evaluated four assigned products for two days each, completing a questionnaire for each sample. The results showed adequate discrimination across products; acceptance for overall liking, aroma, and texture was captured along with perceptions of specific product attributes, product usage, and purchase interest. In addition, non-product related questions were asked to gain a better view of the consumers who participated including psychographic measures, demographics, and general lotion preferences. Integrity of shape (appearance attribute) and several aroma attributes were identified as key driver of liking in both countries. Attributes associated with slow absorption and lasting skin residues, such as oil and amount of residue, were identified as drivers of disliking in both countries. The present work provides a realistic research plan for identifying drivers of liking and successfully achieved its central objectives; this is a valuable building block on which future men’s skin care research can build.
Keywords: Consumer research; Sensory; Descriptive analysis; Skin care